2015
DOI: 10.3109/00365548.2015.1007473
|View full text |Cite
|
Sign up to set email alerts
|

Association of Enterovirus 71 encephalitis with the interleukin-8 gene region in Chinese children

Abstract: The study was performed in 36 Chinese patients with Enterovirus 71 (EV71) encephalitis and 141 patients with EV71-related hand, foot and mouth disease (HFMD) without encephalitis. Genotyping was determined by polymerase chain reaction- restriction fragment length polymorphism. Patients with EV71 encephalitis had a significantly higher frequency of interleukin-8 (IL-8)-251TT genotype than patients with EV71-related HFMD without encephalitis (55.6% vs 31.2%, p = 0.023). The frequency of IL-8-251T alleles was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the EV-A71-infected humanized mice, there was only a subtle increase in the IFN-␥ level, which might account for the absence of pulmonary edema in the humanized mice, although high viral loads and infiltrating lymphocytes were present in the brain and the lung. Recent findings suggested that patients with EV-A71 encephalitis have significantly higher frequencies of IL-8 -251TT genotype and IL-8 -251T alleles than patients with EV-A71-related HFMD without encephalitis, and patients with ANS dysregulation have higher plasma levels of IL-8 than patients with pulmonary edema (32,54). To the best of our knowledge, this is the first report showing that a level of human IL-8 was detected in the EV-A71-infected humanized mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In the EV-A71-infected humanized mice, there was only a subtle increase in the IFN-␥ level, which might account for the absence of pulmonary edema in the humanized mice, although high viral loads and infiltrating lymphocytes were present in the brain and the lung. Recent findings suggested that patients with EV-A71 encephalitis have significantly higher frequencies of IL-8 -251TT genotype and IL-8 -251T alleles than patients with EV-A71-related HFMD without encephalitis, and patients with ANS dysregulation have higher plasma levels of IL-8 than patients with pulmonary edema (32,54). To the best of our knowledge, this is the first report showing that a level of human IL-8 was detected in the EV-A71-infected humanized mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report [38] showed that IL-8 exhibited high AUC values (0.95) through the ROC curve assay and the serum levels of IL-8 in EV71 critical infection (including frequent convulsions, coma, brain hernia, and pulmonary rales) were highest compared with mild cases and severe cases. Both Li et al [52] and Xu et al [37] considered that the frequency of IL-8-251 T alleles among 8 Mediators of Inflammation the severe cases (such as encephalitis and respiratory failure) was significantly higher than that of mild cases. In summary, the studies indicated a strong correlation between IL-8 and EV71-infected HFMD severity.…”
Section: Chemokinesmentioning
confidence: 99%
“…Increasing evidence suggests that inflammatory cytokines may play a central role in HFMD derived from EV-A71 infection 16 18 . It has also been postulated that dysregulation of inflammatory responses and cellular immunity are possibly responsible for this pathogenesis 19 22 .…”
Section: Discussionmentioning
confidence: 99%